Nietzsche and the self: the 'dissolution of the subject in The Man Without Qualities by Robert Musil and disconnected by Oğuz Atay - Talay, Zeynep. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The thesis discusses Nietzsche’s critique of the constitution of the modern self and explores the ways in which this Nietzschean theme appears in literature. I will focus in particular on the Nietzschean theme of the dissolution of the subject as it appears in The Man without Qualities by Robert Musil (1880-1940) and The Disconnected by O"uz Atay (1934-1977). In the first chapter I investigate Nietzsche’s critique of the modern constitution of the self and his own account of the self. In Chapter II, I treat Nietzsche's account of the self as an important background to The Man without Qualities, and in Chapter III, I do the same for The Disconnected. In doing this I not only attempt to indicate the positive meaning of the dissolution of the subject in these novels, but also seek to demonstrate how even experimental or exploratory approaches to the living of a life set limits to such an idea.
Keywords: Self in literature.